2012
DOI: 10.4018/jbir.2012040103
|View full text |Cite
|
Sign up to set email alerts
|

The More, the Merrier?

Abstract: Business intelligence (BI) is a term that refers to a variety of techniques and software applications used to analyze an organization’s raw data. Companies use BI to improve decision-making, identify opportunities, and cut cost. However, implementing a BI system is challenging. Critical success factors (CSFs) are necessary elements for a project to succeed. The aim of this article is to identify critical CSFs and find possible interrelationships. Using a framework of CSF constructs, the authors conducted a qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The Olbrich et al (2012) study made no distinction between the types of BI projects, attempted to include a wide as possible spectrum of industries, and limited the number of participants per industry. Other researchers (Presthus et al 2012;Yeoh & Koronios 2010) identified similar factors that contributed to BI implementation success in different industries.…”
Section: Hypothesis 2 Sub : Alignment Of Project Specific Critical Success Factors Between Projectsmentioning
confidence: 92%
See 2 more Smart Citations
“…The Olbrich et al (2012) study made no distinction between the types of BI projects, attempted to include a wide as possible spectrum of industries, and limited the number of participants per industry. Other researchers (Presthus et al 2012;Yeoh & Koronios 2010) identified similar factors that contributed to BI implementation success in different industries.…”
Section: Hypothesis 2 Sub : Alignment Of Project Specific Critical Success Factors Between Projectsmentioning
confidence: 92%
“…Over the last five years, there have been several empirical studies on CSFs in BI (Yeoh et al 2007;Hawking & Sellitto 2010;Yeoh & Koronios 2010;Olbrich et al 2012;Presthus et al 2012). In these studies, committed top manager support, source system data quality and user involvement emerged consistently as the most important CSFs.…”
Section: Critical Success Factors For Business Intelligencementioning
confidence: 99%
See 1 more Smart Citation
“…Further, the information given by the traditional BI is commonly delivered in static reports with rows and columns which in the past is sufficient and acceptable for support the decision making within organization. Nevertheless, since rapid development of data science has continued immensely, particularly on the frontiers of machine learning and deep learning, nowadays companies seek a new solution to explore raw data combined with powerful and sophisticated analytic tools to gain insights for better decision making (Presthus & Canales, 2015). Their decisions are no longer have to be made in the row or column but more into visual based on evident experiments and more accurate forecasts.…”
Section: Introductionmentioning
confidence: 99%